William Tappan autograph collection - Tappan, William, 1863-
Correspondence, poetry, miscellaneous documents, rare printed matter, prints, photographs, and letters to Tappan, chiefly autographic in nature. Relates chiefly to the Baltimore, Md.-Washington, D.C., area from the War of 1812 through the early twentieth century. Includes correspondence and other items from John C. Calhoun, Josephus Daniels, Robert Gilmor, Edward Everett Hale, Robert Goodloe Harper, John Eager Howard, Edward Ingle, Samuel Smith, Israel Thorndike, and Sir Anthony Van Dyck.
Autograph collector.
Collection material in English, with Dutch.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index available in the Library of Congress Manuscript Reading Room and at
Keywords: Calhoun, John C. -- 1782-1850.; Daniels, Josephus, -- 1862-1948.; Gilmor, Robert, -- 1748-1822.; Hale, Edward Everett, -- 1822-1909.; Harper, Robert Goodloe, -- 1765-1825.; Howard, John Eager, -- 1752-1827.; Ingle, Edward, -- 1861-1924.; Smith, Samuel, -- 1752-1839.; Thorndike, Israel, -- 1755-1832.; Van Dyck, Anthony, -- Sir, -- 1599-1641.; Autographs -- Collections; Baltimore (Md.) -- History; Maryland -- History; Washington (D.C.) -- History; Collectors, Autograph